Implementation of Elementary School Mathematics Questions Based on Numeracy Literacy - Puguh Darmawan; Purna Bayu Nugroho; Vivi Darmayanti (Riemann: Research of Mathematics and Mathematics Education, 2025)
The purpose of this research was to know the implementation of numeracy literacy-based questions in schools. The research method used in this research is descriptive research, namely a type of research that aims to provide an overview of a certain phenomenon. The data collection instrument was a questionnaire. The research period was in June-July 2023, consisting of students in grades 4, 5 and 6 of SDN 1 Sidorejo. The research data was analyzed descriptively quantitatively in the form of percentages. The research results showed that the question statements given by the teacher were carried out using arithmetic operations, 81% often and 19% rarely. Question statements in the form of reading or descriptions was always 64.5% and often 35.5%. The question statement was accompanied by a graph, 87% rarely and 13% never. The question statements were accompanied by a table, 71% often and 29% rarely. The question statements were accompanied by pictures, 48% frequently and 52% rarely. The question statements were accompanied by a diagram, 9.5% always, 81% often, and 9.6% rarely. The question statement required making estimates or conjectures, 6.5% often, 29% rarely, 64.5% never. The question statement required determining how to solve the problem in the question, 19.4% always, 42% often, 25.8% rarely, and 12.6% never. Based on the results of the analysis above, the using of literacy questions in learning activities was still not optimal. This can be seen from aspects of literacy-based questions that were still not fully implemented.